2022
DOI: 10.3390/gels8110711
|View full text |Cite
|
Sign up to set email alerts
|

Low Release Study of Cefotaxime by Functionalized Mesoporous Silica Nanomaterials

Abstract: As a third-generation β-lactam antibiotic, cefotaxime shows a broad-spectrum with Gram-positive and Gram-negative bacteria activity and is included in WHO’s essential drug list. In order to obtain new materials with sustained release properties, the present research focuses on the study of cefotaxime absorption and desorption from different functionalized mesoporous silica supports. The MCM-41-type nanostructured mesoporous silica support was synthesized by sol–gel technique using a tetraethyl orthosilicate (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As a result, we found that the scaffold we developed released the antibiotic more slowly and for a longer duration. It is thought that a bioeliminable scaffold that offers controlled and slow drug release may be more effective on biofilm and more successful in the treatment of osteomyelitis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we found that the scaffold we developed released the antibiotic more slowly and for a longer duration. It is thought that a bioeliminable scaffold that offers controlled and slow drug release may be more effective on biofilm and more successful in the treatment of osteomyelitis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given attractive characteristics like a uniform hexagonal pore structure, high surface area, biocompatibility, excellent chemical stability, high loading capacity, and tunable mesoporous diameters (2-50 nm), MCM-41 and SBA-15 have been widely used in medical applications, such as manufacturing drug carriers and controlled release systems. 12,13 To understand the adsorption and release of antibiotic molecules from mesoporous silica materials, Nairi et al studied the ampicillin from SBA-15 or MCM-41 with different pore sizes or surface charges due to surface functionalization. 14 The authors proposed that both adsorption and release of ampicillin were mainly affected by the surface charge rather than the pore size.…”
Section: Introductionmentioning
confidence: 99%
“…The slow-release profiles were obtained by using an on-flow modified HPLC system. A significant improved release capacity was identified in the case of MCM-41/APS/GA—cefotaxime due to the covalent surface grafting of the biological active compound, recommending this class of materials as an effective carrier of bioactive compounds in wound dressing, anti-biofilm coatings, advanced drugs, and other related applications [ 4 ].…”
mentioning
confidence: 99%